EFFECTIVENESS OF USING INFORMATION TECHNOLOGY IN LEARNING CASE STUDY OF INTERACTIVE LEARNING SYSTEM IN CLASS A EDUCATIONAL TECHNOLOGY - Hasni, Hasni; Sampelolo, Rigel (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study evaluates the effectiveness of information technology in interactive learning among college students. Data was obtained through the questionnaire, showing that information technology in interactive learning is very effective. Most students responded positively to accessibility, flexibility, interactivity, engagement, self-support, and variety of learning materials. Expressly, 100% of students agreed with the questions about these benefits. However, there were differences of opinion on several aspects. Regarding the suitability of learning speed and style, only 72.7 % of students felt that this system was suitable for their needs, while 27.3% thought it needed more. In addition, 90.9 % of students stated the ease of use and effectiveness of interaction, but some were still dissatisfied with these aspects. The conclusion of this study shows that although most students feel positive benefits from using information technology in learning, several areas need improvement, such as adjusting the speed and style of knowledge and the system's ease of use. Recommendations from this study include increasing system flexibility, optimizing interface design, and providing additional support for students. These findings can be a reference for developers of interactive learning systems and educational institutions who want to integrate information technology into the learning process more effectively.